A comparison of parent and child perspectives about barriers to and facilitators of bicycle helmet and booster seat use. Issue 3 (2nd July 2020) - Piotrowski, Caroline C.; Warda, Lynne; Pankratz, Curt; Dubberley, Kate; Russell, Kelly; Assam, Harriet; Carevic, Mateja
Abstract: To date, little work has compared similarities and differences between parent and young people's perceptions of barriers to and facilitators of bicycle helmet and booster seat usage. Our goal was to conduct such a comparison in order to inform future safety campaigns. Eleven focus groups with a total of 68 parents and 11 focus groups with a total of 76 young people were conducted. Recruitment was conducted and focus groups were held in diverse neighbourhoods to facilitate participation by families from a variety of cultural, linguistic, and socioeconomic backgrounds. Overall, parents and their children agreed on 50% of the barriers identified for bicycle helmet use and approximately 40% of the barriers for booster seats. Barriers common to both types of equipment for parents and children included comfort, style and design, and fear of teasing. Common facilitators included perceived safety, and comfort. While there was considerable overlap between the perspectives of parents and young people, there were also differences, underscoring the importance of addressing both perspectives. The barriers and facilitators identified were modifiable to a large extent; based on these, recommendations for future injury prevention campaigns were outlined.